ANALYSING SHIP RESPONSE IN LONG CRESTED SEA IN WEST AFRICA OFFSHORE - Tuboala Emmanuel Akono; Elakpa Ada Augustine; Godspower Obioma Nwaorgu (International Journal of Innovations in Engineering Research and Technology, 2022)
The responses of a typical barge are critical to marine operation and especially its crew. This response can be analyzed in the seaway medium, which could be in the form of sea energy in long crested wave. Hence, the comparative analysis of the vessel response in both sea state is paramount research interest. This research compares the response of the vessel in heave mode with regard to long crested waves. Strip theory and Lewis conformal mapping were used to compute the two-dimensional added mass and damping coefficient. Rhinoceros and AutoCAD software packages were used to model the vessel, which generated 43 strips and the corresponding offset table. Froude Kryloy force and hydrostatic pressure force which form the excitation force were computed simultaneously for the response in long crested with varying directional spread using Runge Kutta 4th order equation with the aid of Mat lab. The study confirms that the linear strip approach is valid for heave response of vessel in long crested waves for length ratio not exceeding six. However various seaways was shown in this research. Even with different headings the discrepancy in the various seaway was minimal and at 0.4 rad/s the heave response tended to zero